Psychological Security Of The Single Mother From The Point Of View Of The Psychologist (a Field Study In Some Algerian Wilayas) - Bougherza, Redha; Boulfelfel, Brahim; Hanoune, Soumia (المجلة الجزائرية للأمن الإنساني, 2021)
This study aimed to identify the level of psychological security among single mothers from the psychologist's point of view, focusing on the following dimensions: life satisfaction, psychological comfort, social stability, social appreciation, using a descriptive approach. To achieve the objectives of the study, a questionnaire composed of (56) statements was administered to a randomly selected sample of (30) psychologists. The data were processed using the statistical software package for the social sciences (spss). The study revealed that: The level of psychological security of single mothers is average. The level of life satisfaction of single mothers is average. The level of psychological comfort of single mothers is average. The level of social stability of single mothers is average. The level of social appreciation of single mothers is average.